The effect of menstrual cycle on anaerobic power and jumping performance - Yapici-Öksüzoglu, A.; Egesoy, H. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. There has been a significant increase in the participation levels of women in competitive sports in recent years. This has contributed to the increase of research on women's participation in sports and their health. The aim of this study is to investigate the effect of the menstrual cycle on anaerobic power and jumping performance. Material and Methods. In this study, 15 female athletes between the ages of 18-24, who have a regular menstrual cycle for the last 6 months Wingate Anaerobic Power Test and Active Jumping Test applied to athletes during their menstrual phases (second day of the menstruation period) and follicular phases (14th day of the menstruation period). In the statistical analysis of the data, descriptive analyses of test measurements of athletes were calculated as mean and standard deviation. Whether there is a significant difference between the measurements taken on two different days was analyzed using the t-test in dependent groups. Results. It was determined that the anaerobic power and active jump performances of the participants had an effect on peak power, fatigue index and active jump performance between day 2 and day 14 values. Also, there was a statistically significant difference between these values (p<0.05). Conclusions. This situation can be explained as a result of the hormonal changes in the menstrual period of the athletes and the effects of psychological factors specific to this period.